The use of prescribing indicators to measure the quality of care in psychiatric inpatients. Issue 1 (2nd February 2004) - Paton, C; Lelliott, P
Abstract : Objective: To explore the potential for using seven prescribing indicators, individually and in combination, to measure prescribing quality for hospitalised psychiatric patients. Design and setting: The dataset included full details of all psychotropic medication prescribed over a 24 hour period to 4192 inpatients in 49 British mental health services in 1998. Results: Despite the large size of the dataset, for three of the indicators 20 services had fewer than 10 eligible patients. There was great variation between services in indicator scores. Correlations between standardised indicator scores and total score (which omitted the indicator concerned) were above 0.3 for all but one of the indicators. Cronbach's alpha was 0.73 when this outlying indicator was removed. Conclusions: There are no routinely collected prescribing data that allow for the quality of prescribing for psychiatric patients to be monitored. Six of the seven indicators measured during this census survey appear to reflect a common attribute of the services, and the analysis suggests that they might be combined to give an overall measure of service performance. There was, however, no relationship between performance on the seventh indicator and performance on the other six. This raises questions about case mix and service level factors that might influence indicator scores independent of prescriber decision making. The psychometric properties of prescribing indicators (occurrence rates, consistency over time) are unknown.